Fuzzy PID Algorithm-Based External Carbon Controller for Denitrification Process Enhancement in Wastewater Treatment Plant - Gutama Indra Gandha; Dedi Nurcipto (JURNAL INFOTEL, 2018)
The water scarcity and drought challenge are the current issue that faced by many countries in the world. The water scarcity and drought have disadvantageous impact to agriculture, industry and the environment. Wastewater reuse method has recognized as solution to overcome water scarcity. Wastewater treatment plant (WWTP) is a widely known as water replenishment that using wastewater reuse system that integrates microbial decomposition to process the wastewater. The over limit of effluent level leads to degradation of water quality produced by the plant. The denitrification process enhancement is highly recommended to increase the quality of water disposal. The adding of carbon material has recognized as a method to enhance the denitrification process. The rising of operational cost of the plant is the direct effect of the using of carbon addition. The high-performance controller is highly suggested to control the flow of carbon material in order to enhance the denitrification process and optimizing the carbon material usage. The PID controller is widely used in industrial purposes. Due the nonlinearity and complexity of the waste water treatment plant makes the traditional PID unable to work appropriately. The real-time error correction must be performed to minimize the error. It could be achieved by combining Fuzzy controller and traditional PID controller. The Fuzzy-PID controller has been succeeded to reduce the usage of the carbon than PID controller. The implementation of Fuzzy-PID controller is able to save the usage of carbon consumption by 412 kg COD. The nitrogen concentration, aeration energy and pumping energy also decreased by 0.0029 mg N/L,87kWh and 17 kWh.